Complementary not competing quality standards. Issue 5 (September 2015) - Rees, Jonathan
<x xml:space="preserve">Abstract</x> The recently published NICE Prostate Cancer Quality Standard differs from the quality statements developed by Tackle Prostate Cancer and described in the previous article. Jonathan Rees explains how the two are complementary and can sit comfortably alongside each other.